IMPLEMENTASI KOMUNIKASI PEMASARAN DIGITAL POLITEKNIK NEGERI MEDIA KREATIF JAKARTA DALAM PROSES PENERIMAAN MAHASISWA BARU TAHUN AKADEMIK 2018-2021: Marketing Communication, Polimedia, AIDA, New Students - eno, trisna_rudi; Oktaviana Purnamasari; Mohammad Ismed; Imanuel Ronald David Mongkau (Politeknik Negeri Media Kreatif, 2024)
The State Polytechnic of Creative Media, also known as Polimedia, is a state vocational higher education institution located in Jakarta. As a state vocational education institution, Polimedia participates in national admissions for new students, such as the National Selection for State Polytechnic Entrance (SNMPN), Joint Selection for State Polytechnic Entrance (SBMPN), the National Selection for State Higher Education Entrance (SBMPTN) specifically for applied bachelor's programs, and the Independent Exam conducted by Polimedia itself. The purpose of this research is to identify the marketing steps taken by Polimedia in recruiting prospective new students. This is closely related to the planning of the marketing communication concept implemented by Polimedia. The AIDA marketing communication model applied by Polimedia is very interesting to study in a research context. Through a qualitative approach and descriptive method, along with observation and in-depth interviews with sources, the steps Polimedia takes in implementing the AIDA concept can be understood. The result is an achievement for Polimedia, which has seen an increase in the number of prospective students wishing to enroll in Polimedia from year to year. More than 8,000 people compete for 2,000 seats at Polimedia—a significant impact. Keyword: Marketing Communication, Polimedia, AIDA, New Students